Pembrolizumab combined with anlotinib improves therapeutic efficacy in pulmonary sarcomatoid carcinoma with TMB-H and PD-L1 expression: a case report and literature review - Wu, Shugui; Wu, Shanlian; Liao, Xiaohong; Zhou, Chaoming; Qiu, Feng; Wang, Chen; Zhong, Wenjuan (Frontiers in Immunology, 2023)
Background: Pulmonary sarcomatoid carcinoma (PSC) is a unique subtype of non-small cell lung cancer (NSCLC) with a high degree of malignancy and poor therapeutic effects. With the widespread use of immune checkpoint inhibitors (ICIs) in recent years, few studies have reported that immunotherapy is effective against PSC. As a multi-target anti-vascular targeting agent, anlotinib showed a better anti-tumor effect in various cancer species. The paper reported the therapeutic and side effects of pembrolizumab combined with anlotinib in a patient with advanced PSC.Case presentation: This is a 73 year old female patient who underwent thoracoscopy right upper lobectomy and was diagnosed as locally advanced PSC. However, the patient experienced tumor recurrence and metastasis 7 weeks after surgery and was unable to tolerate chemoradiotherapy.Moreover, she detected TP53 mutation and found that tumor mutation burden (TMB) and PD-L1 were high expression. Therefore, the patient received pembrolizumab combined with anlotinib treatment. After 15 cycles of treatment, the tumor significantly shrank with no tumor activity. The evaluation of tumor efficacy is partial response (PR). During the treatment period, she experienced one-degree thyroid-stimulating hormone elevation and two-degree hand-foot syndrome.Pembrolizumab and anlotinib was continued for two years as a maintenance treatment. The patient had a good quality of life and no disease progression was observed. Currently, the patient is still alive without tumor progression and has overall survival exceeding 45 months and toxic side effects were tolerable.ICIs and anti-angiogenic targeted therapy has brought new hope in treating advanced PSC. Additionally, TMB and PD-L1 expression could be potential predictive biomarkers of the efficacy in advanced PSC with immunotherapy.